validation of the NEECHAM confusion scale for intensive care delirium assessment - Hossein Ashtarian; Nasrin Mehrabi; Mohammad-Rafi Bazrafshan; Mahmoud Rahmati (Journal of Health Sciences and Surveillance System, 2019)
Introduction: Delirium measurement instruments should be highly sensitive, and their instruction for the users should also be short-term and straightforward. The objective of the present study was to investigate the validation of the NEECHAM confusion scalein predicting the delirium of ICU patients in Kermanshah health care and educational centers in 2015. Methods: This is cross-sectional descriptive-analytic research that was conducted in 2015. The researcher acquired the consent of the administrators of Imam Reza (AS) and Taleqani hospitals. A briefing session was held in ICU units, and the objective and method of the study were explained to patients to attract their cooperation. Sampling was done using convenience sampling. Some 166 patients were selected. The NEECHAM confusion scalewas used to investigate the delirium of patients. The area under the receiver operating characteristic (ROC) curve was used to assess the quality of the questionnaire. The significance level was considered 0.05. Results: Results show that 50.6 percent of the samples were female, and most of them were married (85.2%). Most of the patients lived in cities (78.9%) and were illiterate (50.3%). Also, most of the patients were housewives (44.4%). Instruments for data collection were demographic questionnaire and the NEECHAM confusion scale. The results of this study indicated that 45.2 percent of people have delirium. The NEECHAM confusion scalehas a large area under the ROC curve. Therefore, it has high predicting power in the prediction of delirium. Conclusion: according to the findings of this study, it can be said the NEECHAM confusion scalehas the validity to be able to provide accurate and rapid information about patients' delirious status. Since the cognitive impairment screening tools require regular editing; therefore, nurses working in intensive care units can use this tool to diagnose patients with delirium and prevent delirium complications quickly.